Keyword and named entity recognition on air traffic control (ATC) data - Thia, Jeremy Ming Xuan (2019)
This project will explore several NLP tasks to perform named entity recognition on Air Traffic Control data, to be specific Air Traffic conversations. We will use a Bi-LSTM-CNN-CRF based custom named entity system to detect the entities. A demonstration of the working model will be presented as well.